Negotiating masculinity in a female-dominated industry: experiences of male early childhood educators in Singapore - Lim, Ming Chong (Nanyang Technological University, 2023)
This project aims to better understand the effects of gender at work – specifically in the early childhood industry, where men are the minority in a female-dominated industry. By drawing on gender concepts of masculinity and traditional gender roles, in-depth interviews were conducted to better understand how male educators “do” gender at both the micro and macro levels. From this study, we find that male educators in Singapore negotiate their masculinity by focusing on their professional role as an educator by living up to the ideals and restrictions of being a male educator, while also embracing the feminine traits of nurturing and caring associated with early childhood teaching.